О роли трематод рода Proctoeces Odhner, 1911 в некоторых прибрежных биоценозах Черного моря - Мачкевский, В.К.; Парухин, А.М. (Вестник зоологии, 1981)
Cercaria milfordensis U z m a n n, 1953, causes mass death of the black Sea mussels (Mytilus galloprovincialis). Experiments on infestation of the Black Sea crustaceaus (Myzidae gen. sp., Palaemon elegans, Gammarus olivia, Idotea baltica basteri, Haetogaster marmoratus) and molluscs (Rissoa splendida, Hidrobia arenarum, Nana donovani, Byttium reticulatum) with these cercariae show that metacercariae develop only in Rissoa splendida. The rest of crustaceans and molluscs cannot be additional hosts of the Proctoeces genus trematodes, but actively eliminate cercariae: the amount of C. milfordensis is regulated by the mentioned species of invertebrates.